PERKEMBANGAN DAN STIMULASI KEAKASARAAN ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL 4 BANJAR REJO - Aulia Rahma; Aulia Arda Sabila; Nurmeiyati; Pita Dwi Aprilia; Siska Ayu Lestari (STPI Bina Insan Mulia Yogyakarta, 2023)
Literacy learning is a process of stimulating, guiding, nurturing and providing play activities that are meaningful, safe, comfortable and fun according to the child's developmental stage. The purpose of this study was to find out how the development and stimulation of children's literacy in Group B TK ABA 4 Banjarrejo. The type of research used was descriptive qualitative research, with the research subject being group B which consisted of 18 children consisting of 8 boys and 10 girls. Data collection techniques using observation techniques, interviews, and documentation. The results of the study showed that children in Kindergarten ABA 4 Banjarrejo could stimulate literacy development with the learning methods provided, namely storytelling, singing, charades and letter card media. The results of the study showed that there was a significant increase in the development of children's literacy skills with the result that 98% were well developed and 2% were not well developed.